2018
DOI: 10.1155/2018/5156812
|View full text |Cite
|
Sign up to set email alerts
|

Lead Environmental Pollution and Childhood Lead Poisoning at Ban Thi Commune, Bac Kan Province, Vietnam

Abstract: Lead poisoning is a public health problem in many areas of the world. Children are at particularly high risk for adverse effects of lead exposure; even at low concentrations, lead can affect physical, mental, and behavioral development. Children living near lead-zinc mines are at high risk for environmental lead poisoning, especially the contaminated soil. We conducted a cross-sectional descriptive study in Ban Thi Commune, northern Vietnam. 195 children (92,9% participation) aged 3-14 years old (average: 7.69… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Luo et al [ 17 ] surveyed a total 1,379 children in three areas near lead and zinc mining sites in China (2017), and found that the median blood lead concentration was 6.6 µg/dL, and that 341 children (24.73%) showed blood lead concentrations higher than 10 µg/dL, and that blood lead concentrations decreased as the age of children increased. A study conducted in Zambia (2015) showed an inverse correlation between the distance from lead and zinc mining sites and the blood lead concentration in children [ 18 ], and a study conducted in Vietnam (2018) showed an inverse correlation between the lead concentration in the soil, groundwater, and house dust, and the distance from sources of contamination [ 19 ]. On the other hand, in this study, no difference in lead concentration in children's blood was observed according to the distance of residence from the mine.…”
Section: Discussionmentioning
confidence: 99%
“…Luo et al [ 17 ] surveyed a total 1,379 children in three areas near lead and zinc mining sites in China (2017), and found that the median blood lead concentration was 6.6 µg/dL, and that 341 children (24.73%) showed blood lead concentrations higher than 10 µg/dL, and that blood lead concentrations decreased as the age of children increased. A study conducted in Zambia (2015) showed an inverse correlation between the distance from lead and zinc mining sites and the blood lead concentration in children [ 18 ], and a study conducted in Vietnam (2018) showed an inverse correlation between the lead concentration in the soil, groundwater, and house dust, and the distance from sources of contamination [ 19 ]. On the other hand, in this study, no difference in lead concentration in children's blood was observed according to the distance of residence from the mine.…”
Section: Discussionmentioning
confidence: 99%
“…Emisi industri juga merupakan sumber penting kontaminasi timbal pada tanah dan udara sekitar (Liang & Ghaffari, 2014). Timbal dari udara atmosfer atau cat terkelupas yang disimpan di tanah dan debu dapat dicerna oleh anak-anak dan secara substansial dapat meningkatkan kadar timbal darah mereka (Hai et al, 2018). Selain itu, makanan dan air juga bisa menjadi media penting untuk paparan awal terhadap timbal (Brown & Margolis, 2012).…”
Section: Pendahuluanunclassified
“…As a result of EPA's regulatory efforts including the removal of Pb from motor vehicle gasoline, levels of Pb in the air decreased by 98% between 1980 and 2014 (Hai et al 2018). Still high level of Pb pollution is an important issue in Lucknow.…”
Section: Analysis Of Air Quality Datamentioning
confidence: 99%